Effect of pollination TIME on yield and quality of Date fruit - M. Iqbal; S. A. Jatoi; M. Niamatullah; M. Munir; I. Khan (Journal of Animal and Plant Sciences, 2014)
The effects of pollination at different day time in date cv. Dhakki were investigated at Date-palm Research Orchard, Gomal University Dera Ismail Khan during 2008-2009. The six spathes on the selected Dhakki trees were pollinated at one hour interval from 8 am to 4 pm. Data were recorded for fruit set (%), fruit weight (g), fruit length (cm), fruit breadth (cm), fruit drop (%)  and yield (kg). Pollination at different day time had significant effect on the fruit setting and other quality parameters. The highest fruit set of 91% and 89.87%, fruit weight of 18.00 g and 18.34 g, fruit length of 4.75 cm and 4.72 cm and fruit thickness of 2.89 cm and 2.61 cm in both years were recorded when pollination was carried out at 12:00 pm. A consistent trend was observed during the two years. Pollination carried out at 12:00 pm found to be the most effective for getting better yield, fruit setting and fruit size. In addition, positive and significant correlation was observed among different parameters, which can provide basis for further improvement in yield and quality of dates.
Keywords: Dhakki; Pollination Time; Fruit Set; Fruit Drop; Yield Traits